Math, asked by adityapote217, 3 months ago

In PPQRS, side RQ ll side RS and side QR ll sides PS prove that ∆ PQR = ∆RSP​

Attachments:

Answers

Answered by jasveersingh31
2

Answer:

By SAS congruency PQR =RSP

Step-by-step explanation:

As oppose. side are parallel so it is a llgm .

in tri. PQR and RSP

PS = RQ ( OPPO. side are equal)

PQ =RS. ( same )

ang. SPR = ang. RSP ( alternate Interior Angle)

hence,

TrianglePQR = TriangleRSP

Answered by Anonymous
0

Given that:-

  • Quadrilateral PQRS
  • RQ // RS
  • QR // PS

Prove :-

  • ∆ PQR = ∆ RSP

In ∆ PQR and ∆ RSP

  • PS = QR (:. Opposite sides)
  • PQ = RS (:. Opposite sides)
  • Angle PQR = Angle RSP (:. Alternate interior angles)

By SAS congruency,

  • ∆PQR ≅ ∆PSR ✔️

Hence proved

  • ∆PQR = ∆RSP
Attachments:
Similar questions